Floral biology and its manipulation for successful breeding programs in cassava (Manihot esculenta Crantz) - A review - M N, Sheela; Hegde, Vivek; K M, Senthilkumar; P V, Abhilash; S, Amalnath (JOURNAL OF ROOT CROPS, 2024)
Cassava is an important staple food of the tropical regions, and it fulfils the dietary requirements of ~900 million people. It is a strategic crop with climate resilience, wide adaptation to diverse climatic conditions and has the potential to cope with the effects of climate change in the future. Cassava is a cross-pollinated crop, pollinated mainly by honey bees. Speed breeding incassava is constrained by its high levels of genetic heterozygosity, sparsely flowering nature of genotypes with high breeding value and low seed set as well as seed germination. In India, cassava breeding was successfully carried out during the last five decades through selection of profusely flowering genotypes, manipulation of flowering in sparsely flowering genotypes using mechanical methods and hormonal treatment. There is variation in flowering time (from 4 months to >eight months) and the number of flowers among genotypes. Different genotype-environment interaction existed on flowering among varieties and a strong environmental effect on the number of flowering peaks within the same variety was noticed. Induction of flowering in erratic flowering types was done through pruning/de-topping of non branching types and by grafting on to profusely flowering clones. Cryopreservation of pollen of sparsely flowering genotypes was successfully undertaken to maximise the genetic recombination in cassava. The present paper summarises the floral behaviour of cassava in different mating systems and artificial induction of flowering and cryopreservation of pollen that was successfully used to develop hybrids, inbreds and triploids in cassava.